P637Desmin null mouse as a possible experimental model of arrhythmogenic cardiomyopathy. (15th July 2014) - Athanasiadis, N; Katsiboulas, M; Dimitriou, C; Kostavassili, I; Mavroidis, M; Davos, CH
Abstract: Background: Desmin null mice (Des-/-) develop a multisystem disorder involving cardiac, skeletal, and smooth muscle. Myocardial abnormalities include progressive degeneration, cardiomyocyte death, extensive calcification and fibrosis which lead to a dilated cardiomyopathy pattern. The aim of this study is to investigate the presence of arrhythmias in a Des-/- mouse model as compared to wild type (WT) mice. Methods: Mice lacking desmin were generated by gene targeting via homologous recombination as previously describe. Electrocardiographic (ECG) recordings were obtained in 8-months old Des-/- and WT mice (n=17) using a Data Sciences International Telemetry System (St. Paul, MN, USA). ECG data were collected for 5 min every 30 min for 24 consecutive hour, giving 240 min of recording. Arrhythmias were recorded and heart rate, QRS wave duration and PR and QTc (Bazett's formula) intervals and were measured using Ponemah software. Mice also underwent a swimming stress test protocol of 20min total duration under ECG recording. Results: Premature ventricular beats were more often in Des-/- mice (n=16, 85.5±37.9/240min, range 0-612) when compared to the WT (n=8, 3.9±1.3/240min, range 0-15). Heart rate (523±20 vs 566±19 bpm), QRS (16.9±1.3 vs 17.0±0.9 ms) and PR duration (37.1±1.1 vs 34.1±1.5 ms, p=0.07) did not differ between Des-/- and WT mice. Only QTc interval was prolonged in Des-/- mice compared to the WT (186.1±5.9 vs 173.3±3.6 ms, p=0.04). Supraventricular ectopic beats were only present in Des-/- mice (range 3-111). During endurance, more premature ventricular beats were observed in Des-/- mice (range 14-510) compared to the WT (range 2-14) but first and second degree AV block were only present in Des-/- mice. Conclusion: Ventricular and supraventricular arrhythmias are common in Des-/- mice compared to the WT making this genetic model a possible experimental model of arrhythmogenic cardiomyopathy.